Utilization of Solar Panel Technology to Save Electricity Costs in Fish Farm Irrigation - Nisrina, Safira Fegi; Mudzakir, Mohammad Alfian; Rahmat, Basuki (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Solar panels are a medium that can convert solar energy into electrical energy. In this research, the solar panel system in the fish pond is used as air requirements for the survival of the fish so that the air supply is sufficient. The problem is that fish farming has cloudy water due to decreasing temperatures due to lack of irrigation. This condition really requires water flow using a pump to circulate water in the fish pond. Therefore, solar panels are needed to drive the water circulation pump, where these solar panels are an alternative energy source to replace electricity from the State Electricity Company (PLN).The purpose of using a solar panel system is as alternative energy that can supply a pump motor which functions to channel water from the well to the pond to keep it flowing. This is used as alternative electrical energy to replace energy sources originating from the State Electricity Company (PLN) and to reduce operational costs of electrical energy. The method used is to assemble and install 2 units of 100WP solar panels, then testing is carried out to measure the panel output power from 06.00 to 17.00. The average result of measuring solar panel power every 30 minutes is 24.48Watts per day, this condition was when the test was carried out when the weather was less sunny. However, this can still change to get maximum power depending on weather conditions, especially when the sun is hot.